2013
DOI: 10.1128/jb.00644-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of RibN, a Novel Family of Riboflavin Transporters from Rhizobium leguminosarum and Other Proteobacteria

Abstract: bRhizobia are symbiotic bacteria able to invade and colonize the roots of legume plants, inducing the formation of nodules, where bacteria reduce atmospheric nitrogen (N 2 ) to ammonia (NH 3 ). Riboflavin availability influences the capacity of rhizobia to survive in the rhizosphere and to colonize roots. In this study, we identified the RL1692 gene of Rhizobium leguminosarum downstream of a flavin mononucleotide (FMN) riboswitch. RL1692 encodes a putative transmembrane permease with two EamA domains. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 46 publications
(60 reference statements)
1
55
0
2
Order By: Relevance
“…In light of our earlier flavoproteome analysis , it is remarkable that E. coli has multiple targets for this antibiotic. Recently, the first riboflavin transporter from a Gram‐negative bacterium was identified , raising the hope that roseoflavin or flavin analogs in general could become useful for also treating infections with Gram‐negative bacteria. Our studies with E. coli certainly provide a solid basis for the development of novel antibacterials with novel targets.…”
Section: Discussionmentioning
confidence: 99%
“…In light of our earlier flavoproteome analysis , it is remarkable that E. coli has multiple targets for this antibiotic. Recently, the first riboflavin transporter from a Gram‐negative bacterium was identified , raising the hope that roseoflavin or flavin analogs in general could become useful for also treating infections with Gram‐negative bacteria. Our studies with E. coli certainly provide a solid basis for the development of novel antibacterials with novel targets.…”
Section: Discussionmentioning
confidence: 99%
“…Flavins used by this protein may be transported into the cell by the putative membrane protein encoded by CLJU_c19430, which contains two EamA domains like the characterized riboflavin-transporting transmembrane permeases (RibN) from Ochrobactrum anthropi and Vibrio cholerae (90). A blastx query of the putative epimerase gene (CLJU_c19420) in this oxygen-induced gene cluster revealed that it had higher homology to a phenazine biosynthesis-like protein than its annotated function as an epimerase.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding COG3601, COG0697, COG3201, and TauC family proteins are also commonly associated with FMN riboswitches. These proteins have been characterized as riboflavin transporters in various organisms (Vogl et al 2007;García Angulo et al 2013;Gutiérrez-Preciado et al 2015).…”
Section: Variant Rnas Have Key Characteristics That Differ From Typicmentioning
confidence: 99%